Knotweed (Fallopia spp.) Invasion of North America Utilizes Hybridization, Epigenetics, Seed Dispersal (Unexpectedly), and an Arsenal of Physiological Tactics. (March 2016) - Gillies, Sharon; Clements, David R.; Grenz, Jennifer
Abstract: More than 100 years ago, Japanese knotweed was introduced to North America. Given its vigorous rhizome system and capability to grow from rhizome and stem fragments, it persists and spreads locally, forming monotypic stands. The Japanese knotweed clone originally introduced was a male sterile female clone; thus, early in the invasion, reproduction from seed was not an issue. The implication was that long-distance dispersal was relatively rare. However, recently, widespread hybridization between Japanese knotweed and Sakhalin (giant) knotweed has been reported, with the hybrid species, Bohemian knotweed, forming the majority of knotweed plants in many areas and possessing higher variability than the parent species. The hybrids produce large numbers of wind-dispersed viable seeds that germinate at rates approaching 100% in some populations. As temperatures increase, knotweed is predicted to expand its range farther north and to higher elevations. With the ability to regenerate from vegetative fragments and disperse via seeds, invasive knotweed species are on the move. An arsenal of chemical weapons, the ability to shade out competitors, and the ability to adapt rapidly through epigenetic change makes knotweed a formidable invader. We observed that knotweed species clearly possess 8 of the 12 ideal weed characteristics, with Bohemian knotweed likely exhibiting still more because of prolific seed production. More research is needed to answer pressing questions. How does hybridization affect knotweed epigenetics? Under what conditions might seed production become more frequent? What kind of niche expansion is possible with the increased variability? Given the considerable challenges posed by knotweed species that promise to become even greater with the proliferation and spread of Bohemian ecotypes, only a thoroughly researched, well-informed approach to knotweed management across North America can be successful.